Local and landscape composition affect southern flying squirrel distributions along their western range edge - Robbins, Lydia (My University, 2026)
Range-limiting processes are complex for mammal populations and not always dictated by environmental constraints (e.g., elevation, climate). Land-use changes at range edges, such as agricultural or woody encroachment into prairies, can either facilitate or preclude species expansions. In Kansas, USA, eastern deciduous forests abruptly transition into tallgrass prairie landscapes and delineate the western edge of the southern flying squirrel (Glaucomys volans, hereafter ‘flying squirrels’) geographic range. It is unclear, however, how southern flying squirrel distributions are structured in this dynamic landscape positioned at their range edge. We investigated how both local- and landscape-scale characteristics influenced habitat use by flying squirrels along their range edge using three years of detection/non-detection data (2023-2025) from camera-trap arrays at 300 sites. Southern flying squirrels were detected at 53 of the 300 sites (naïve occupancy 0.18). Our most-supported single-season occupancy model indicated that, on a local-scale, flying squirrels are more likely to occur at sites with more hard-mast trees, greater tree richness, and greater canopy over. At the landscape-scale, flying squirrels were more likely to occur at sites surrounded by more forest cover and less grassland cover. Our results provide the first efforts to quantify contemporary distributions of southern flying squirrels along their western range edge where landscape and environmental changes are pervasive. Additionally, our results suggest southern flying squirrel western range edges may be structured more by dynamic landcover features rather than abiotic factors.
Keywords: Camera-trap; Ecological drivers; Fragmentation; Forest structure; Habitat; Occupancy